Criterion for finding the optimal electrocatalyst at any overpotential. (20th December 2021) - Zhang, Yufan; Huang, Jun; Eikerling, Michael
ABSTRACT: The generic volcano plot is a widely employed practical tool to display and compare the activity of different electrocatalysts in dependence of a small number of descriptors. It is known that the apex of the volcano curve shifts with applied potential. However, the trend of the potential-dependent shift of the volcano apex has remained unclear. Herein, we address this question for a two-step electrocatalytic reaction. With the transfer coefficient assumed as 1/2, our analysis reveals that the adsorbate coverage at the volcano apex equals 1/2 regardless of potential. We present a criterion to predict the direction and magnitude of the apex shift as a function of the activation energies of the two steps. Thereafter, the criterion is extended to the oxygen reduction reaction. The influence of the transfer coefficient and the potential of zero charge on the volcano plot is revealed. Implications of the presented criterion for targeted design of electrocatalysts are discussed.